An efficient construction of key-dependent substitution box based on chaotic sine map. (December 2019) - Usama, Muhammad; Rehman, Osama; Memon, Imran; Rizvi, Safdar
A substitution box is a core component of the popular symmetric-key algorithms. However, the major problem of the conventional substitution boxes is the statistic behavior, which is employed as a fixed-size lookup table. To solve the fixed-size lookup table problem, various substitution box construction methods were proposed with key control, but it is hard to enhance all cryptographic properties, for example, linear and differential probabilities. Thus, chaos is applied for key control in designing robust substitution boxes due to unpredictable and random-like behavior. Moreover, the confusion and diffusion properties of cryptography can be achieved by chaos. This article introduces an efficient construction of a key-dependent substitution box based on the mixing property of the chaotic sine map. The substitution box so constructed has very low differential and linear approximation probabilities. The experimental results confirmed that the proposed method to construct substitution box has acceptable cryptographic properties to resist against various cryptanalysis.